PENINGKATAN KOMPETENSI PEDAGODIK GURU MELALUI PELAKSANAAN SUPERVISI KLINIS DENGAN TEKNIK KELOMPOK - Babuta, Asma Is; Rahmat, Abdul (JURNAL AL-TANZIM, 2019)
This study aims to find out the picture, find a solution, and increase the pedagogical competence of teachers in 4 junior high schools under the guidance of researchers. The research subjects were Pohuwato district, namely SMPN 2 Wanggarasi, SMPN 2 Dengilo, SMPN 2 Randangan  dan SMPN 3 Marisa. Data collection in this study was carried out by observation, and documentation. In this study data validation was done by triangulation technique. Data analysis starts from the field or empirical facts by going into the field, observing, studying, analyzing, interpreting and drawing conclusions. The results showed that the teacher's pedagogical competence increased from 2 teachers or 9.09% in the pre-cycle, to 10 teachers or 45.45%, and in the last cycle increased to 100% or all teachers were stated to have increased pedagogical competence. This indicates that clinical supervision by school supervisors has proven effective as an effort to improve teacher pedagogical competencies in the 4 Guidance Middle Schools.